2021
DOI: 10.1111/jocn.15709
|View full text |Cite
|
Sign up to set email alerts
|

Nursing interventions for pressure injury prevention among critically ill patients: A systematic review

Abstract: Aim To systemically synthesise the evidence on the most effective nursing interventions to prevent pressure injuries among critical care patients. Background Although pressure injury (PI) prevention is a focus of nursing care in critical care units, hospital‐acquired pressure injuries continue to occur in these settings. Design A systematic review of literature guided by the Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA) and Synthesis without meta‐analysis (SWiM) guidelines. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 52 publications
1
39
0
2
Order By: Relevance
“…For example, fall‐related injuries, medication errors and infections are the most commonly reported adverse events in acute‐care settings in Australia (Australian Institute of Health & Welfare, 2018). Similarly, pressure injuries are considered a preventable adverse event by national and international groups such as the Agency for Healthcare Research and Quality (Alshahrani et al, 2021; Chou et al., 2013), Australian Commission on Safety and Quality in Healthcare (Australian Commission on Safety & Quality in Health Care, 2019) and the US Joint Commission on Accreditation in Healthcare Organizations (The Joint Commission, 2016). Consequently, financial penalties are increasingly being imposed on healthcare providers to acknowledge the gravity and preventability of pressure injuries (Nguyen et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, fall‐related injuries, medication errors and infections are the most commonly reported adverse events in acute‐care settings in Australia (Australian Institute of Health & Welfare, 2018). Similarly, pressure injuries are considered a preventable adverse event by national and international groups such as the Agency for Healthcare Research and Quality (Alshahrani et al, 2021; Chou et al., 2013), Australian Commission on Safety and Quality in Healthcare (Australian Commission on Safety & Quality in Health Care, 2019) and the US Joint Commission on Accreditation in Healthcare Organizations (The Joint Commission, 2016). Consequently, financial penalties are increasingly being imposed on healthcare providers to acknowledge the gravity and preventability of pressure injuries (Nguyen et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…PIs are associated with longer hospital stays, higher hospitalization costs (Nguyen et al, 2015), and prolonged physical or mental health conditions (Gorecki et al, 2012). They can impact the patients' quality of life (Jackson et al, 2017), ultimately increasing morbidity and mortality rates (Alshahrani et al, 2021). Factors associated with PI development in critical care patients include age, mobility/activity, poor perfusion (Alderden et al, 2017), bowel and bladder incontinence, and a moist skin due to fever and diaphoresis.…”
Section: Introductionmentioning
confidence: 99%
“…This was suggested in other meta-analyses, which showed a similar effect of prophylactic sacral protective dressings on preventing pressure injury. [11][12][13][14][15] This requires further investigation and explanation because no clear rationale was found to explain these results. Well-designed studies are also needed to assess the factors including the combination of different ages, gender, and ethnicity, because our meta-analysis study could not answer whether these factors are associated with the results.…”
Section: Discussionmentioning
confidence: 94%
“…4 Numerous meta-analyses have examined the efficacy of prophylactically applied protective dressings. [11][12][13][14][15] A 2013 Cochrane review of prophylactic use of soft silicone foam dressings showed a decrease in pressure injury frequency in numerous studies, with inadequate indication because of the low quality of the comprised studies. 16 In an update to this meta-analysis, the indication was of very low and low graded for high risk of bias and high inaccuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation